2016
DOI: 10.1038/srep23991
|View full text |Cite
|
Sign up to set email alerts
|

Possible association of CCDC62 rs12817488 polymorphism and Parkinson’s disease risk in Chinese population: a meta-analysis

Abstract: Conflicting results identifying the association between coiled-coil domain containing 62 (CCDC62) polymorphism, rs12817488, and Parkinson’s disease (PD) have been reported. To clarify whether rs12817488 is related to PD risk in Chinese population, we carried out this meta-analysis by searching literature from PubMed and Embase database regarding this polymorphism. Three eligible studies involving 1616 cases and 1649 controls were included in this meta-analysis. Our results showed statistically significant asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
(24 reference statements)
0
2
0
Order By: Relevance
“…CCDC62 (coiled-coil domain containing 62) was found to be related to PD susceptibility in the Nalls et al studies conducted in 2011 and 2014 (Nalls et al, 2011 , 2014 ) pointing out two different intron variants. The gene has a role in cell growth, estrogen receptor transactivation, cyclin D1 expression in prostate cancer cells as well as in other varieties of cancer, since its antibodies are often produced and thus detected (Li et al, 2013 ; Lu et al, 2016 ). Until recently, it was mainly reported as related to cancer (Yu et al, 2015 ).…”
Section: Genetic Determinants Of Risk For Sporadic Pd and Their Implimentioning
confidence: 99%
“…CCDC62 (coiled-coil domain containing 62) was found to be related to PD susceptibility in the Nalls et al studies conducted in 2011 and 2014 (Nalls et al, 2011 , 2014 ) pointing out two different intron variants. The gene has a role in cell growth, estrogen receptor transactivation, cyclin D1 expression in prostate cancer cells as well as in other varieties of cancer, since its antibodies are often produced and thus detected (Li et al, 2013 ; Lu et al, 2016 ). Until recently, it was mainly reported as related to cancer (Yu et al, 2015 ).…”
Section: Genetic Determinants Of Risk For Sporadic Pd and Their Implimentioning
confidence: 99%
“…only found this association in a female population [ 57 ]. In summary, several aspects may contribute to the different results between the two studies, including age of onset, EOPD/LOPD ratio, sex ratio, and MAF [ 58 ]. Our previous study also observed a genetic female distribution bias in the mitochondrial genome of PD patients in northern China [ 59 ].…”
Section: Discussionmentioning
confidence: 99%